Torca Wetland Action Plan Analysis, Based on the Strategic Environmental Evaluation (2014)
This paper shows the results of a research carried out, on the Torca Wetland's Action Plan, at Usaquén, Bogotá, based on the Strategic Environmental Assesment, SEA, in order to contribute to the wetland conservation. To achieve it, there were conducted the following phases of SEA: an analysis of the Torca wetland's District Environmental Management, an Environmental assessment, the current state determination of the Wetlands and PAHT's district policy, the Environmental Options Assessment, Prevention and monitoring. The analysis is framed upon a research project, of a Master Degree in Sustainable Development and Environmental Management, at the Bogotá District University, Francisco José de Caldas.